2016
DOI: 10.1002/bmc.3878
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an UPLC‐Q/TOF‐MS assay for the quantitation of neopanaxadiol in beagle dog plasma: Application to a pharmacokinetic study

Abstract: Neopanaxadiol (NPD), the main panaxadiol constituent of Panax ginseng C. A. Meyer (Araliaceae), has been regarded as the active component for the treatment of Alzheimer's disease. However, few references are available about pharmacokinetic evaluation for NPD. Accordingly, a rapid and sensitive method for quantitative analysis of NPD in beagle dog plasma based on ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry was developed and validated. Analytes were extracted from plasma b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(71 reference statements)
2
5
0
Order By: Relevance
“…Although the pharmacokinetic profiles of PPD and PAT were significantly different, obvious double peaks were observed in the concentration–time profiles of both groups, which were consistent with the results of previous pharmacokinetic studies on panaxadiol (Geng et al, 2017). The peak pattern for PPD was consistent with that reported in the literature.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Although the pharmacokinetic profiles of PPD and PAT were significantly different, obvious double peaks were observed in the concentration–time profiles of both groups, which were consistent with the results of previous pharmacokinetic studies on panaxadiol (Geng et al, 2017). The peak pattern for PPD was consistent with that reported in the literature.…”
Section: Resultssupporting
confidence: 90%
“…The T max values of both were less, showing that PPD ginsenosides were mainly absorbed directly into the plasma. Previous study has shown that PPD was rapidly eliminated from the body, with a t 1/2 of 2 h, and the oral bioavailability in rats was about 30% (Bao et al, 2013) Although the pharmacokinetic profiles of PPD and PAT were significantly different, obvious double peaks were observed in the concentration-time profiles of both groups, which were consistent with the results of previous pharmacokinetic studies on panaxadiol (Geng et al, 2017). The peak pattern for PPD was consistent with that reported in the literature.…”
Section: Validation Of the Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…Ginsenosides can be converted into hydrophobic compounds by the intestinal microbial enzymes, and are then transported to the liver, which metabolizes these hydrophobic metabolites into hydrophilic compounds through phase I–III enzymes. Information from the literature concerning the PK studies of ginseng is given in Table S8 † 336,342,346–370 . These studies involve a systematic description of the absorption, distribution, metabolism, excretion, and blood concentration of ginsenosides over time after administering pure compounds (involving Rh4/Rk3, 346 25-OCH 3 -PPD/25-OH-PPD, 347 neopanaxadiol, 348 26-OH-PPD, 349 PPD, 350 24-OH-PPD, 351 Rb3, 352 Rc, 353 noto-Fc, 355 CK, 336 Rb1, 356 octillol/RT5/F11, 357 and Rd 358 ) or ginseng extracts (white ginseng, 342 fermented and nonfermented P. ginseng , 359 red ginseng, 362 P. quinquefolius , 365 and P. notoginseng 366) to healthy humans or animals.…”
Section: Metabolism and Metabolomicsmentioning
confidence: 99%
“…Notably, ginseng berry extract showed a superior oral absorption of ginsenoside Re ( F % 0.33–0.75) at equivalent ginsenoside Re dose to pure ginsenoside Re, indicating that ginseng berry extract might be a good form for ginsenoside Re intake . A rapid and sensitive method is developed and validated for quantitative analysis of neopanaxadiol in beagle dog plasma based on ultra‐performance liquid chromatography quadruple time of flight mass spectrometry (UPLC‐Q‐TOF‐MS) …”
Section: Metabolic Studies Of Ginsenosides Based On Lc‐msmentioning
confidence: 99%